PERANCANGAN KORI AGUNG - Frysa Wiriantari; Gusti Ngurah Semarajaya (Jurnal Anala, 2018)
Traditional Balinese architecture is a masterpiece born of a tradition, belief and spiritual activity of Balinese people embodied in various physical forms such as traditional houses, shrines, meeting halls and others. The birth of various physical manifestations is also caused by several factors, namely geographical, cultural, cultural and socio-economic conditions. Kori Agung as part of Balinese traditional architecture, is one of the entrance types passed down from generation to generation by our ancestors which is a manifestation of Hindu that underlies trust, custom as the norms of life. So there is an effort to preserve it so that the cultural values contained in it do not become faded.Along with the development of time, some demands emerged from the needs of people living towards the entrance, this paper will discuss matters relating to the layout, materials, size and also the philosophical value of the kori agung. By using comparative methods and analysis of several case studies are expected to provide answers to the differences and similarities of the physical manifestation of kori agung in BaliKeywords : kori agung, philosophy , physical form